The Effects of Airway Pressure Release Ventilation on Pulmonary Permeability in Severe Acute Respiratory Distress Syndrome Pig Models - Cheng, Jiangli; Yang, Jing; Ma, Aijia; Dong, Meiling; Yang, Jie; Wang, Peng; Xue, Yang; Zhou, Yongfang; Kang, Yan (Frontiers in Physiology, 2022)
Objective: The aim of the study was to compare the effects of APRV and LTV ventilation on pulmonary permeability in severe ARDS. Methods: Mini Bama adult pigs were randomized into the APRV group (n = 5) and LTV group (n = 5). A severe ARDS animal model was induced by the whole lung saline lavage. Pigs were ventilated and monitored continuously for 48 h. Results: Compared with the LTV group, CStat was significantly better (p < 0.05), and the PaO2/FiO2 ratio showed a trend to be higher throughout the period of the experiment in the APRV group. The extravascular lung water index and pulmonary vascular permeability index showed a trend to be lower in the APRV group. APRV also significantly mitigates lung histopathologic injury determined by the lung histopathological injury score (p < 0.05) and gross pathological changes of lung tissues. The protein contents of occludin (p < 0.05), claudin-5 (p < 0.05), E-cadherin (p < 0.05), and VE-cadherin (p < 0.05) in the middle lobe of the right lung were higher in the APRV group than in the LTV group; among them, the contents of occludin (p < 0.05) and E-cadherin (p < 0.05) of the whole lung were higher in the APRV group. Transmission electron microscopy showed that alveolar–capillary barrier damage was more severe in the middle lobe of lungs in the LTV group. Conclusion: In comparison with LTV, APRV could preserve the alveolar–capillary barrier architecture, mitigate lung histopathologic injury, increase the expression of cell junction protein, improve respiratory system compliance, and showed a trend to reduce extravascular lung water and improve oxygenation. These findings indicated that APRV might lead to more profound beneficial effects on the integrity of the alveolar–capillary barrier architecture and on the expression of biomarkers related to pulmonary permeability.